Distinct clinical correlates of immune thrombocytopenic purpura at diagnosis of childhood-onset and adult SLE. Issue 4 (4th July 2018) - Esteves, Gladys Cherres Xavier; Gormezano, Natali Weniger Spelling; Pereira, Oriany L.; Kern, David; Silva, Clovis Almeida; Pereira, Rosa Maria Rodrigues; Kozu, Katia Tomie; Bonfá, Eloisa; Aikawa, Nadia Emi
Abstract: Objectives: To compare clinical and laboratorial features between childhood-onset systemic lupus erythematosus (cSLE) and adult SLE (aSLE) at concomitant diagnosis of immune thrombocytopenic purpura (ITP). Methods: This study evaluated 56 cSLE and 73 aSLE patients regularly followed at Pediatric and Rheumatology Divisions of the same University hospital with ITP (platelets count <100, 000/mm 3 in the absence of other causes) at lupus onset. Results: Median current age was 11.6 and 27.3 years in cSLE and aSLE, respectively. cSLE had a higher frequency of ITP compared to aSLE (17% vs. 4%, p < .0001) and the former group had more hemorrhagic manifestations (36% vs. 16%, p = .0143). Constitutional symptoms and reticuloendothelial manifestations ( p < .05), as well as pericarditis (25% vs. 10%, p = .029) and central nervous system (CNS) involvement (30% vs. 14%, p = .029) were more common in cSLE. Conversely, in aSLE, ITP was solely associated with cutaneous and articular involvements ( p < .05). Concerning treatment, intravenous methylprednisolone, intravenous immunoglobulin, blood transfusion and platelets transfusion were more frequently used in the cSLE population ( p < .05). Conclusion: ITP at cSLE has distinct features compared to aSLE with a more severe presentation characterized by concomitant constitutional/reticuloendothelial manifestations, CNS involvement and hemorrhagic manifestation. These findings reinforce the need for a more aggressive treatment in this age group.